2021
DOI: 10.2147/jmdh.s330579
|View full text |Cite
|
Sign up to set email alerts
|

English or Arabic in Healthcare Education: Perspectives of Healthcare Alumni, Students, and Instructors

Abstract: Background Using English as a medium of instruction (EMI) in non-English speaking countries to teach healthcare subjects has been questioned in various international healthcare educational contexts, despite the numerous benefits it offers to students and institutions. Purpose The present study collected data to examine the impact of the EMI policy and analyze the experiences of students and instructors in a healthcare course in Saudi Arabia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…Based on the views of participants, there are insufficient Arabic educational materials, and most of the published content learning materials used for teaching and research are in English. This finding aligns with that of Alhamami and Almelhi (2021a) that access to learning materials and research opportunities is the main advantage of the EMI policy because most published learning and research materials are in English; this finding shows that English published materials such as textbooks, websites, audio-visual materials, etc. dominate the market.…”
Section: Advantages Of Emi Policysupporting
confidence: 86%
See 1 more Smart Citation
“…Based on the views of participants, there are insufficient Arabic educational materials, and most of the published content learning materials used for teaching and research are in English. This finding aligns with that of Alhamami and Almelhi (2021a) that access to learning materials and research opportunities is the main advantage of the EMI policy because most published learning and research materials are in English; this finding shows that English published materials such as textbooks, websites, audio-visual materials, etc. dominate the market.…”
Section: Advantages Of Emi Policysupporting
confidence: 86%
“…In the context of universities in Saudi Arabia, Alhamami (2021) reported that (i) Saudi computer-science students preferred to learn computer subjects in Arabic, their native language, and (ii) their societal attitudes and self-efficacy beliefs significantly predicted their preferred MI. In the context of undergraduate healthcare programs, Alhamami and Almelhi (2021a) found that most healthcare students held negative attitudes toward the EMI policy, whereas instructors held more-positive beliefs toward EMI in healthcare programs; the researchers recommended that to design better EMI programs, policymakers should focus on improving students’ English proficiency and understanding stakeholders’ beliefs and attitudes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meaningful learning in learning theory is called meaningful learning, including the meaningful learning theory of Carl R. Rogers and David Ausubel. Meaningful learning or meaningful learning is actually the central idea of David Ausubel's theory which is incorporated in cognitive theory, which is a process in which new information is associated with an aspect of the structure of knowledge (cognitive) that relevant things that students have learned and remembered (Alhamami, 2021). Learning is also meaningful was used as a term by Carl P. Rogers, who joined.…”
Section: Introductionmentioning
confidence: 99%
“…In Egypt, for instance, Sabbour et al (2010) found that the larger number of medicine students have difficulties in studying their courses in English. Likewise, Alhamami and Almelhi (2021) study revealed that healthcare students in Saudi Arabia prefer to study their majors in Arabic as it enhances their understanding and improves their academic achievement. In the Omani context, Al-Masheikhi et al (2014) found that though university students are aware of the status of English as the global language of science and technology, more than half of them opt to use Arabic as a medium for studying their majors.…”
Section: Arguments For and Against The Arabicization Vs Englishizatio...mentioning
confidence: 99%